The Effect of Using Laser Sensor Apparatus for Developing Time and Accuracy of Interpassing in Young Soccer Players - Ali, Mohammed (Journal of Physical Education, 2021)
The importance of the research lies in studying the effect of applying exercises using laser sensor device on the development of time and accuracy in inter passing for young soccer players. The problem of the research lies in interpassing weakness. The research aimed at designing an apparatus for training players as well as preparing exercises. The researcher used the experimental method on 20 players. After two pilot studies, the training program began for (10) weeks with 3 training sessions per week. The data was collected and treated using proper statistical operations to conclude that the apparatus designed by the researcher as well as the exercises were very effective.